(1116) estimation of needs and demands for health services and formulation of the health plan - hassouna, W. A. (the institute of national planning, 2018)
good health is one of an individual's most highly prized possessions. it is a deep and intimate concern. it stands first and foremost as something to be preserved in its own right. regardless of variations in cultural expression,expression, human society gives credence to this view by the various codes which protect the individual's right to life.